Hubungan Number Sense dan Kemampuan Pemecahan Masalah Matematika Mahasiswa Pendidikan Matematika - Wulandari, Nourma Pramestie; Junaidi, Junaidi; Novitasari, Dwi; Triutami, Tabita Wahyu (Griya Journal of Mathematics Education and Application, 2024)
This study aims to analyze the relationship between number sense and mathematical problem-solving abilities among mathematics education students. Number sense refers to an individual's ability to understand basic mathematical concepts intuitively, while problem-solving ability involves applying mathematical knowledge to solve complex problems. This research employs a quantitative approach with a correlational design. Data were collected through number sense tests and mathematical problem-solving tests administered to Mathematics Education students at a university. The results indicate a significant positive correlation between number sense and mathematical problem-solving ability. This suggests that students with good number sense tend to be more effective in solving mathematical problems. This research is expected to contribute to the development of mathematics education curricula by emphasizing number sense as a foundation for enhancing students' problem-solving skills.